Growth of purple nutsedge (Cyperus rotundus) in response to interference with direct-seeded rice - Chauhan, Bhagirath S.; Opeña, Jhoana (Cambridge University Press, 2012)
The biology of purple nutsedge was studied by growing it alone and in competition with 12 and 24 rice plants in a pot experiment. Compared with the weedy plants grown alone, competition from rice reduced purple nutsedge leaf number, shoot number, tuber production rate, and leaf biomass. At 10 wk after planting, interference from 12 and 24 rice plants reduced purple nutsedge leaf area by 79 and 86%, respectively, compared with weedy plants grown without rice interference. On the same date, purple nutsedge aboveground shoot biomass was 26.8 g plant−1without interference, whereas in interference with 12 and 24 rice plants, purple nutsedge produced aboveground biomass of 4.8 and 2.2 g plant−1, respectively. A total of 95 tubers plant−1were produced by purple nutsedge when grown alone. Growth with 12 and 24 rice plants reduced tuber production to 33 and 17 tubers plant−1, respectively. Without interference, purple nutsedge produced 40 g plant−1of total biomass of tuber plus root plus rhizome, whereas in interference with 12 and 24 rice plants, purple nutsedge produced 14 and 5 g plant−1of total belowground biomass, respectively.